1963
DOI: 10.1063/1.1734155
|View full text |Cite
|
Sign up to set email alerts
|

Study of Low-Frequency Molecular Motions in HF, KHF2, KH2F3, and NaH2F3

Abstract: a 19°°• emhs aS 'll-mm-H ■ MW I -»■ • meme warn ■awf -* = ee • wteea e * me-=ee --mee m e -• e= •e eommeeme meme w e-em ee ,ni -s • • Hirns-*-= =meme smee em ememe= -•m mu -4 e == meme eememme mm = • memmevme ms-seme-ma..... as • ee . ........ . •e mr=m ema -•me * e Em-e • ■ii'i ew wm am d m n-msesiw m -es ms aS em emmemme me emm "e BNL 6722 e Study of Lv Frequency Molecular Notions in HF, KHF2» KH2F3 and Nak2F3 + t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…2 shows a (Q, ω)-map of the obtained current spectra j(Q, ω). The intensity around 50-60 meV can be attributed to an isotopically shifted librational mode, which was already observed in the early measurements on HF [12]. The second obvious part is the region of intensity in the small wave vector range up to Q ≈ 2.5 Å…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…2 shows a (Q, ω)-map of the obtained current spectra j(Q, ω). The intensity around 50-60 meV can be attributed to an isotopically shifted librational mode, which was already observed in the early measurements on HF [12]. The second obvious part is the region of intensity in the small wave vector range up to Q ≈ 2.5 Å…”
Section: Resultssupporting
confidence: 61%
“…Furthermore, lines at 25 and 30 meV could be identified which have been related to in plane translational movements. By neutron scattering an inelastic mode at 67 meV and at 27 meV was observed in solid HF [12]. In the liquid state the high energy mode remained, but the lower one seems to disappear to a weak shoulder.…”
Section: Introductionmentioning
confidence: 92%
“…[23]) and in the crystal (2.25 from ref. [24]). It is closer to the FÀF distances observed or computed in polyfluoride F(HF) n À ions, since these distances increase with n from 2.29 to 2.50 (see for example refs.…”
Section: Structure Of the Liquidmentioning
confidence: 99%
“…The two former structures are displayed in Figure 1. Later, several studies using IR, Raman, and NMR spectroscopies and inelastic neutron scattering experiments were undertaken [4], but were unable to settle the issue as to the position of the hydrogen atom. Finally, in 1975, the structure was investigated with the neutron powder diffraction method by Johnson et al [5] and the structure was found to be polar.…”
Section: Introductionmentioning
confidence: 99%